Spiritual Education in Postmodern Society - Aramavičiūtė, Vanda (Acta Paedagogica Vilnensia, 2004)
In this article spiritual education is grounded on relevancy of modern society. The advantages and disadvantages of postmodernism and its influence on the individual Psychical and spiritual development are disputed. Spirituality is described as the object of spiritual development. According to the viewpoint of theologians, philosophers and educators, spirituality is defined as an individual’s relation with the world, which is based on highest values which are derived from the truth, the good, beauty and holiness. The 1998 research results based on senior school learners’ spiritual development are taken into consideration, what makes Spiritual development aims and objectives of senior school age are presented relevant.